Water-beads Ingestion with Intestinal Obstruction in Children: A Case Report - Nicodemus; Irma Susanti, Nuraini (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Foreign body ingestion often occurs in the pediatric population and can cause no symptoms or even cause complications due to swallowing the foreign body. The aim of this case report is to increase clinician knowledge of cases of foreign body ingestion which can cause complications. Case: We report a case of foreign body ingestion water beads with complications of intestinal obstruction in a 1 year 2-month-old girl. The patient came with complaints of vomiting more than ten times containing fluid accompanied by decreased intake. The patient was suspected of swallowing water beads. The patient came to the emergency room with no signs of acute abdomen and the results of plain abdominal radiograph showed no foreign objects. The patient began to show symptoms of obstruction, not being able to defecate and not being able to pass gas. Physical examination revealed abdominal distention accompanied by inaudible bowel sounds. Abdominal CT scan results showed ileal obstruction. An exploratory laparotomy was performed, and two water beads were found intraoperative, which were the cause of the obstruction. The foreign body was removed. After surgery, the patient experienced gradual clinical improvement until he was discharged ten days after the procedure. Discussion: Foreign body ingestion in children is often not witnessed by anyone and may not cause symptoms until complications such as obstruction or peritonitis occur. Some foreign objects are radiolucent in plain radiographs. In emergency cases of foreign body ingestion, it is necessary to carry out emergency endoscopic procedures, even emergency surgical procedures in cases that cause complications. Conclusion: This case report increases clinician knowledge and awareness regarding the clinical approach in evaluating patients with suspected foreign body ingestion in children.